A CW-type zinc finger protein is involved in RES-oxylipin signaling and the response to abiotic stress in Arabidopsis thaliana - Lange, Manuel; Korte, Arthur; Fuchs, Maximilian; Fekete, Agnes; Mueller, Claudia; Dierich, Barbara; Witte, Jannis; Dandekar, Thomas; Mueller, Martin J.; Berger, Susanne (Frontiers in Plant Science, 2025)
IntroductionOxylipins regulate the response of plants to biotic and abiotic stress factors and the tolerance of unfavorable conditions. While the signaling pathway of jasmonic acid has been intensively studied, little is known about the signal transduction that mediates the responses of reactive electrophile oxylipins such as 12-oxo phytodienoic acid and prostaglandins.Methods and resultsHere, a CW-type zinc finger protein (ZIFI1, At3g62900) was identified as a new signaling factor in a mutant screen. Transcriptome analysis of Arabidopsis mutants with a defect in this gene showed that the zinc finger protein is involved in regulating gene expression. Only about half (327 genes) of the about 646 genes induced by the reactive electrophilic oxylipin prostaglandin in the wild type was also up-regulated in the zifi1 mutant. The differentially expressed genes are enriched in genes related to detoxification and responses to stress factors such as oxidative stress. Therefore, it was tested whether a defect in the zinc finger gene resulted in altered sensitivity to stress factors. The sensitivity to the reactive oxygen species butyl hydroperoxide and to the xenobiotic triiodobenzoic acid was increased in the mutant. In addition, production of reactive oxygen species induced by the bacterial elicitor flg22 was accelerated.DiscussionThe results provide new insights into the factors involved in the signaling of reactive electrophiles and the connection of different stress signaling pathways.